PENGARUH PERPUTARAN PIUTANG TERHADAP TINGKAT LIKUIDITAS PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA RAHARJA KABUPATEN BANDUNG - Hernawati, Euis; Ikhsan, Sugiyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This study aims to analyze the influence of receivable turnover on the level of liquidity at PDAM Tirta Raharja Bandung Regency. This research method using quantitative method. Data collection techniques used are observations and literature review. Data analysis techniques used are linier regression analysis, product moment correlation and coefficient of determination. Data analysis shows that the correlation coefficient of -0,716 which means the relationship between receivable turnover on the level of liquidity at PDAM Tirta Raharja Bandung Regency is strong, with R square are 51,26%.